2012
DOI: 10.1111/j.1365-2044.2012.07235.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radial and ulnar blood flow after radial artery cannulation with 20‐ and 22‐gauge cannulae using duplex Doppler ultrasound

Abstract: SummaryThis study evaluated ulnar and radial artery blood flow after radial artery cannulation during general anaesthesia using Doppler ultrasound. A total of 80 patients were randomly assigned to receive radial artery cannulation with either a 20-G or 22-G cannula. Arterial diameter, peak systolic velocity, end-diastolic velocity, resistance index and mean volume flow were measured at four time points in both arteries: before anaesthesia; 5 min after intubation; immediately after cannulation; and 5 min after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Second, some studies have shown the presence of recruitable vascular reserve in the hand that can prevent clinically evident ischemia after mechanical manipulation of the radial artery. 27,28 This concept is supported clearly by studies that show the safety of using the homolateral ulnar artery for access in patients with occluded or unavailable radial artery access. 29,30 Finally, no substantial numbers of isch emic complications were reported in our study or in other RCTs that evaluated transradial access.…”
Section: Discussionmentioning
confidence: 51%
“…Second, some studies have shown the presence of recruitable vascular reserve in the hand that can prevent clinically evident ischemia after mechanical manipulation of the radial artery. 27,28 This concept is supported clearly by studies that show the safety of using the homolateral ulnar artery for access in patients with occluded or unavailable radial artery access. 29,30 Finally, no substantial numbers of isch emic complications were reported in our study or in other RCTs that evaluated transradial access.…”
Section: Discussionmentioning
confidence: 51%
“…The RA cannulation under general anesthesia results in a marked compensatory increase in the ipsilateral UA blood flow . The compression of RA at the wrist level increases the blood flow and peak velocity of UA .…”
Section: Discussionmentioning
confidence: 99%
“…When the radial artery diameter decreased by more than 20% of the pre-cannulation diameter, we noted cannulation-induced vasospasm. 10 Ultrasonographic measurements were obtained using a LOGIQe TM instrument (GE Healthcare, Wauwatosa, WI, USA) with a linear probe (12L-RS, 8-13 MHz) by a single experienced operator.…”
Section: Methodsmentioning
confidence: 99%